Altruism and Professional Performance of Teachers in Ugandan Private Secondary Schools - Musa, Muwaga; Nashori, Fuad (Journal An-Nafs: Kajian Penelitian Psikologi, 2024)
This study investigates the relationship between altruism and teacher performance in private secondary schools in Iganga District, Uganda—a context that remains underrepresented in existing literature. While previous research has explored altruism within corporate and public service sectors, limited attention has been paid to its role in non-profit educational environments, particularly in Sub-Saharan Africa. To address this contextual and content-related gap, a mixed-methods approach was employed, combining a cross-sectional survey design with both quantitative and qualitative techniques. Data were collected from 88 respondents, including head teachers and teachers with administrative responsibilities, using validated questionnaires and semi-structured interviews. Quantitative data were analyzed using Pearson product-moment correlation, while qualitative insights were interpreted through content analysis. The results reveal a statistically significant and strong positive relationship (r = .644, p < .01) between altruism and teacher performance. Qualitative findings further illuminate how altruistic behaviors—such as empathy, collaboration, and voluntary support—contribute to sustained performance and institutional cohesion. The study offers a novel contribution by demonstrating how altruism functions as a critical behavioral factor in enhancing teacher effectiveness in resource-constrained school settings. These findings underscore the importance of cultivating altruistic values in school management practices and teacher development programs. Future research should explore comparative analyses between school types and examine institutional support mechanisms that sustain altruism.